PENGARUH WAKTU SIMPAN SEMEN SEGAR DENGAN PENGENCER ANDROMED PADA SUHU RUANG TERHADAP KUALITAS SEMEN KAMBING BOER - Try Puji Lestari; M Nur Ihsan; Nurul Isnaini (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
This research was conducted from 20th Mei to 10th June 2014 at Sumber Sekar Field Laboratory Animal Husbandry Faculty Brawijaya University Malang. The aims of this experiment was to test the effect of semen storage duration diluted with Andromed solution at room temperature on the quality of  Boer goat spermatozoa. The material was 1 boer goat semen aged 3 years old. Methods  used experimental Randomized Design with 6 treatment and 10 replications by used Completely Randomized Design. The interval storage duration were 0, 60, 120, 180, 240 and 300 minutes. Data was analysed by analysis of variance. The result showed that  interval storage duration of Boer goat semen diluted with Andromed solution were highly significant different (P<0,01) on sperm individual motility, sperm viability and sperm abnormality percentage. Optimal time for AI was 300 minutes at room temperature with 40±4,08% of individual motility and 57,94±1,71% of viability percentage.  Optimal time for AI was 300 minutes in room temperature with 13,20±0,20% of sperm abnormality. The conclusion of this result was Boer goat semen diluted with Andromed at room temperature should be used not more than 300 minutes.   Keyword: Boer goat, sperm motility, viability and sperm abnormality